TAREKAT-TAREKAT DI KALIMANTAN SELATAN ( Alawiyyah, Sammniyyah dan Tijniyyah ) - Asmaran Asmaran (Pascasarjana UIN ANTASARI Banjarmasin, 2013)
There is no doubt that islamization of Nusantara can not be separated from significant role of sufism. The term